2021
DOI: 10.3390/su14010207
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Face Masks as a Long-Term Source of Microplastics in Recycled Urban Green Waste

Abstract: Following the outbreak of the COVID-19 pandemic in March 2020, many governments recommended or mandated the wearing of fitted face masks to limit the transmission of the SARS-CoV-2 virus via aerosols. Concomitant with the extensive use of non-sterile, surgical-type single-use face masks (SUM) was an increase of such masks, either lost or discarded, in various environmental settings. With their low tensile strength, the spunbond and melt-blown fabrics of the SUM are prone to shredding into small pieces when imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
2
29
0
2
Order By: Relevance
“…Many of the masks encountered in urban greenspaces and roadside verges originated on curbside parking and would have been blown to the locations by the wind as well as by vehicular draught. While most masks discarded/lost on roads and in carparks would eventually be removed by street cleaners, masks deposited in greenspaces remained in situ unless they were caught during mowing operations [9]. Once in the environment, the masks underwent processes of environmental decay.…”
Section: Environmental Decay Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the masks encountered in urban greenspaces and roadside verges originated on curbside parking and would have been blown to the locations by the wind as well as by vehicular draught. While most masks discarded/lost on roads and in carparks would eventually be removed by street cleaners, masks deposited in greenspaces remained in situ unless they were caught during mowing operations [9]. Once in the environment, the masks underwent processes of environmental decay.…”
Section: Environmental Decay Processesmentioning
confidence: 99%
“…The majority of masks were encountered in carparks and at curbside parking locations where they were lost or discarded while entering or exiting parked vehicles. While the majority of these masks were removed during street cleaning operations, a significant quantity of masks was found in urban green spaces, in particular, on the verges of roads and footpaths, where they entered the green waste stream through mowing [9] or decayed in place. Decaying single use facemasks shed large amounts of microfibers into the environment as their bonds break.…”
Section: Introductionmentioning
confidence: 99%
“…Single use PP masks are usually made of three fabric layers: (a) the outer water-repellent layer (spun bound, non-woven fabric) that provides mechanical strength and protection; (b) middle layer (also a non-woven, melt-blown fabric with high porosity for breathability) that intercepts water droplets; (c) the inner layer (soft fibers by filament spinning and thermal bonding) that is similar to the outer one. The edges are made of heat-wielded seams with two elastic ear loops (Dutton 2008; Spennemann 2022 ; Fadare and Okoffo 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that PP masks released into the urban environment are relatively easily fragmented into smaller pieces due to various physical effects ( e.g. lawn cutting equipment) ( Spennemann 2022 ). Since disposable PP masks are made of fibers ( Aragaw 2020 ), they release secondary MPs into the environment at a much higher rate than plastic boxes or bags due to heat or solar radiation ( Ma et al, 2021 , Shen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation